The struggle for safety: effectiveness of caterpillar defenses against bird predation. Issue 4 (3rd October 2014) - Lichter‐Marck, Isaac H.; Wylde, Micah; Aaron, Eric; Oliver, Jeffrey C.; Singer, Michael S.
<x xml:space="preserve">Abstract</x> The effectiveness of anti‐predator traits, such as warning signals and camouflage, has rarely been quantified from a phylogenetic community ecology perspective. Here we use a phylogenetic comparative analysis to test the association between several putative anti‐predator traits and bird predation risk in an assemblage of caterpillar species. We synthesize eight years of field and laboratory study of a temperate forest community, including a four‐year bird exclusion experiment that provided comparative measures of bird predation risk for 38 caterpillar species from a phylogenetic community. We then conducted a phylogenetic generalized least‐squares and information‐theoretic model selection analysis of warning signals (aposematism or mimicry), camouflage (crypsis or masquerade), and behavioral responses to physical attack as predictors of bird predation, while also accounting for putatively important effects of the abundance, mean body size, and phenology of caterpillar species. The most behaviorally specialized caterpillar species possessing warning signals experienced the lowest bird predation risk, supporting aposematism theory and highlighting the role of prey behavior in the visual signaling of predators. Among the camouflaged caterpillar species, those with the greatest latency to detection by human proxy predators experienced the lowest bird predation risk, supporting camouflage theory. Caterpillar behavioral responses to physical attack, however, predicted increased bird predation risk among camouflaged caterpillars. Although caterpillar abundance, body size, and phenology were expected to be important based on inference from optimal foraging theory and previous field observations, these factors had limited predictive power. This study provides methodologically unique evidence for the importance of morphological and behavioral components of primary, visual defenses of caterpillars against their avian predators in a natural community.